Tantangan Investasi Jateng: Pembenahan Infrastruktur dan Reformasi Birokrasi - Adi Ekopriyono Adi Ekopriyono (FEB UNTAG Semarang, 2013)
The main challenges of local government (both Central Java provincial and district/city governments in Central Java) to increase investment, are: the infrastructure improvement and bureaucratic reform. It is recorded in the results of a series of competitiveness surveys, namely the Business Climate Survey (BCS) 2007, Regional Competitiveness Survey in Central Java 2010, Snapshot Survey 2011, and Investment Survey 2012. Therefore, provincial and district/city government should consistently prioritize the use of the budget for infrastructure improvements and reform the bureaucracy seriously, making conducive business climate. The improved investment performance will give a “multiplayer effect” on reducing unemployment and poverty.